Measuring spatial concentration: A transportation problem approach. Issue 3 (3rd November 2019) - Ferrante, Mauro; Lo Magno, Giovanni Luca; De Cantis, Stefano; Hewings, Geoffrey J.D.
Abstract: This paper will propose an index for measuring spatial concentration, which is based on the solution of a particular transportation problem. This approach extends a new index proposed for the measurement of seasonality to the spatial case, and it takes into account the level of the concentration of the phenomenon of interest according to its spatial distribution. Various properties of the proposed index, which make it a desirable measure for spatial concentration, will also be described. An empirical application, using data from selected European countries, will be provided, and the results derived from the proposed index will be compared with those derived from currently used indices. Resumen: Este artículo propone un índice para medir la concentración espacial, que se basa en la solución de un problema particular de transporte. Este enfoque extiende el uso de un nuevo índice propuesto para la medición de la estacionalidad al caso espacial, y tiene en cuenta el nivel de concentración del fenómeno de interés en función de su distribución espacial. También se describen varias propiedades del índice propuesto, que lo convierten en una medida deseable para la concentración espacial. Se proporciona una aplicación empírica, para la cual se utilizan datos de países europeos seleccionados, y los resultados derivados del índice propuesto se comparan con los derivados de los índices utilizados actualmente. 抄録: 本稿では空間的集中度を測定する指標を提案する。この指標は、ある交通輸送の問題の解決法を基にしている。このアプローチは、シーズナリティを測るために提案したこの新しい指標を空間的事例にまで拡張するものであり、空間的分布によって関心事象の集中度のレベルを考慮に入れるものである。また、空間的集中度を理想的に測定する、この指標の様々な特性を説明する。ヨーロッパの一部の国のデータを用いて、実証的な応用を実施し、新しい指標から得られた結果と従来の指標による結果とを比較する。